2021
DOI: 10.1002/dmrr.3458
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in mood symptoms ​after post‐bariatric surgery among people with obesity: A systematic review and meta‐analysis

Abstract: Aims We aimed to examine if bariatric surgery was associated with a reduction in the prevalence of depressive and anxiety symptoms among people with obesity. Materials and Methods We pooled data from 49 studies involving 11,255 people with obesity who underwent bariatric surgery. The study outcomes were the prevalence of depressive and anxiety symptoms among these patients pre‐ and post‐surgery. Results There was a significant reduction in body mass index (BMI) post‐operatively (pooled d+: −13.3 kg/m2 [95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
(126 reference statements)
2
18
0
Order By: Relevance
“…Although this improvement may hold true, depression severity did increase after 2–3 years post-surgery, as shown in a meta-analysis of 58 studies [ 69 ]. Our longitudinal design provided confirmatory data that bariatric surgery offers short-term but not long-term improvements in depression and anxiety, supporting the proposed notion of a ‘psychological honeymoon‘ period of 3 years post-surgery, followed by rebounds in anxiety, depressive symptoms and binge eating disorder, as reported in other studies [ 22 ]. We recommend that all bariatric surgical candidates receive preoperative education and psychiatric evaluation as to the possibility of mental illness.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although this improvement may hold true, depression severity did increase after 2–3 years post-surgery, as shown in a meta-analysis of 58 studies [ 69 ]. Our longitudinal design provided confirmatory data that bariatric surgery offers short-term but not long-term improvements in depression and anxiety, supporting the proposed notion of a ‘psychological honeymoon‘ period of 3 years post-surgery, followed by rebounds in anxiety, depressive symptoms and binge eating disorder, as reported in other studies [ 22 ]. We recommend that all bariatric surgical candidates receive preoperative education and psychiatric evaluation as to the possibility of mental illness.…”
Section: Discussionsupporting
confidence: 88%
“…Many previous studies have not reported progressive and combined measures (both medication use and blood tests) of obesity-related comorbidities over a long-term period [ 3 , 20 , 21 ]. A recent systematic review showed that the effects of bariatric surgery on mental health conditions are contradictory [ 22 ]. High rates of mental health conditions are relatively common in patients with extreme obesity—as high as 30–40% in bariatric surgery candidates [ 23 , 24 ]—yet long-term data, particularly beyond 3 years post-surgery, are also limited on mental illness after bariatric surgery [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) are the most effective treatments for severe obesity and generally lead to sustainable improvements in weight, glycemic control, and other aspects of physical health. 1 4 Bariatric surgical procedures are also associated with improvements in mental health, 5 , 6 self-esteem, 7 , 8 body image, 9 , 10 sexual desire, 11 and comfort with physical intimacy. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, EPM301 has shown impressive results in treating neuro-behavioral conditions such as anxiety and nausea, demonstrating efficacy at lower doses compared to CBDA [ 28 ], and major depression [ 29 ]. Accordingly, depression was linked to obesity in different studies [ 30 , 31 , 32 , 33 ]. Hence, an intriguing question is whether EPM301 can be used to treat DIO and GIO.…”
Section: Introductionmentioning
confidence: 99%